Pengaruh Digitalisasi terhadap Kinerja Karyawan melalui Kepuasan Kerja sebagai Variabel Intervening - Bendelina Amalya Welkis; Tarsisius Timuneno; Ria E. I. Nafie; Ni Putu Nursiani (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to analyze the effect of digitalization on employee performance with job satisfaction as an intervening variable at PT. ASDP Indonesia Ferry (Persero) Kupang Branch. The research employs an associative quantitative approach, focusing on the relationships between variables and testing previously formulated hypotheses. A sample of 67 employees was selected using simple random sampling based on Slovin's formula, with probability sampling as the sampling technique. Data were collected through questionnaires, interviews, observations, and documentation. The analysis was conducted using SPSS version 22 to examine both the direct effect of digitalization on employee performance and the indirect effect mediated by job satisfaction. The results indicate that digitalization has a positive and significant impact on employee performance. Furthermore, job satisfaction serves as an intervening variable that strengthens the influence of digitalization on improving employee performance. These findings underscore the importance of effective digitalization management and enhancing job satisfaction to support organizational goals in the era of digital transformation